2011
DOI: 10.1592/phco.31.12.1257
|View full text |Cite
|
Sign up to set email alerts
|

Nephrotoxicity Associated with Intravenous Colistin in Critically Ill Patients

Abstract: The frequency and severity of colistin-induced nephrotoxicity in critically ill patients was consistent with previous reports in non-critically ill patients. Most cases of nephrotoxicity demonstrated in this study were mild and reversible. Patients receiving colistin therapy who have hypertension or chronic kidney disease should be monitored closely, and administration of additional nephrotoxic agents should be avoided in all patients when possible. Large, prospective trials are warranted to confirm these resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
65
2
7

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 17 publications
5
65
2
7
Order By: Relevance
“…Numerous studies have evaluated the prevalence of colistinassociated nephrotoxicity, but the rates vary widely in the literature, ranging anywhere from 10% to 48% (3)(4)(5)(6). The reasons for such wide variability are multifactorial.…”
mentioning
confidence: 99%
“…Numerous studies have evaluated the prevalence of colistinassociated nephrotoxicity, but the rates vary widely in the literature, ranging anywhere from 10% to 48% (3)(4)(5)(6). The reasons for such wide variability are multifactorial.…”
mentioning
confidence: 99%
“…In some studies, concomitant NSAID or vancomycin use, hypertension, and older age were identified as independent risk factors for colistin-induced AKI (6,14,24,25), whereas these findings were not corroborated in several other studies, including ours (10,13,17,19,25,26).…”
Section: Discussionmentioning
confidence: 65%
“…The rates of colistin-induced AKI reported in the literature vary between 11z and 53.5z (3,4,6,9,10,(13)(14)(15)(16)(17). This variability could be attributed to the dose and duration of the therapies, and to the varying definitions of AKI.…”
Section: Discussionmentioning
confidence: 99%
“…Lamentablemente los estudios que buscaron analizar la incidencia de toxicidad renal para esta polimixina, carecen de uniformidad en las definiciones de falla renal, y esto mismo explica que se describan valores que fluctúan, en general, entre 10-50% [66][67][68][69][70][71][72][73][74][75][76][77] . No obstante lo anterior, es probable que actualmente la frecuencia de nefrotoxicidad sea más baja, ya que contamos con mejores unidades de pacientes críticos y preparados farmacéuticos más puros 78,79 .…”
Section: Toxicidadunclassified